Investigation of composition and structure of tripoliphosphate coating on low carbon steel - Vlasova, Elena; Kovalenko, Vadym; Kotok, Valerii; Vlasov, Sergey; Sknar, Irina; Cheremysinova, Anna (Eastern-European Journal of Enterprise Technologies, 2017)
The hypothesis on the matrix (composite) structure of the iron (III) tripolyphosphate precipitate and polyphosphate coatings on the steel substrate has been justified experimentally. According to the hypothesis, that iron (III) tripolyphosphate acts as a matrix forming agent while water-soluble sodium tripolyphosphate corrosion inhibitor is a filler. Be means of the chemical synthesis method, it has been demonstrated that the chemical basis of the coating formed on the steel surface in the STPP solution is iron (III) tripolyphosphate. It has been established that the composite structure of tripolyphosphate coatings and precipitates is determined by the nature of iron (III) tripolyphosphate. The conducted investigation on the composition of the iron (III) tripolyphosphate precipitate and tripolyphosphate coating on steel, using the gravimetric method with washing have proved the presence of STPP. The results of X-ray spectral analysis have revealed that STPP in the structure of composite coating is situated not only as a filler inside the matrix but also as an additional layer on its surface. The chemical protection mechanism of the tripolyphosphate coating on steel in atmospheric conditions has been justified. The acquired knowledge would expand the theoretical and practical concept of the structure and properties of tripolyphosphate coatings on the steel substrate and their protection mechanism in conditions of atmospheric corrosion. The application of new knowledge in researches aimed at the development of ecologically safe methods of tripolyphosphate coating deposition with estimated complex of properties, would increase their efficiency.